Effects of milling methods on tensile properties of polypropylene / oil palm mesocarp fibre biocomposite - Ahamad Nordin, Noor Ida Amalina; Ariffin, Hidayah; Hassan, Mohd Ali; Ibrahim, Nor Azowa; Shirai, Yoshihito; Andou, Yoshito (Universiti Putra Malaysia Press, 2015)
The objective of this study was to evaluate the effects of milling methods on tensile properties of polypropylene (PP) / oil palm mesocarp fibre (OPMF) biocomposites. Two types of mills were used; Wiley mill (WM) and disc mill (DM). Ground OPMF from each milling process was examined for its particle size distribution and aspect ratio by sieve and microscopic analyses, respectively. Results showed that DM-OPMF had smaller diameter fibre with uniform particle size compared to the WM-OPMF. Surface morphology study by SEM showed that DM-OPMF had rougher surface compared to WM-OPMF. Furthermore, it was found that PP/DM-OPMF biocomposite had higher tensile strength compared to PP/WM-OPMF, with almost two-fold. Thus, it is suggested that small diameter and uniform size fibre may improve stress transfer and surface contact between the fibre and polymer matrix and cause welldispersion of filler throughout the polymer resulted in better tensile strength of PP/DM-OPMF compared to PP/WM-OPMF biocomposite. Overall, it can be concluded that disc milling could serve as a simple and effective grinding method for improving the tensile properties of biocomposite.